Можливості використання в Україні позитивного зарубіжного досвіду щодо взаємодії між органами публічного адміністрування та суб’єктами підприємницької діяльності - Іняхін, В. Є.; Iniakhin, V. Ye. (Європейські перспективи. - 2023. - № 1. - С. 206-212, 2023)
Узагальнено позитивний зарубіжний досвід взаємодії між органами публічного адміністрування та суб’єктами підприємницької діяльності. Виокремлено позитивний досвід таких країн, як: США, Німеччина, Польща, та опрацьовано можливості його використання в контексті покращення взаємодії між органами публічного адміністрування та суб’єктами підприємницької діяльності в Україні.

Attention is focused on the fact that in different countries there are certain differences in the interaction between public administration bodies and subjects of entrepreneurial activity. Thus, in the USA, the participation of entrepreneurs in charitable activities is quite widespread, it is an important element of the latter’s “behavior”, part of their positive image, which is also combined with significant tax discounts. In European countries, stimulation of the charitable activities of entrepreneurs by public administration bodies takes place in the format of their normative and imperative obligation. For example, significant importance is attached to the work of local public administration bodies in Poland, particularly in the context of information provision and stimulation of business investments. It is summarized that the most promising for implementation in Ukraine is the following foreign experience regarding the interaction between public administration bodies and business entities: first, tax incentives for philanthropy of business entities due to an increase in the percentage of the tax discount; secondly, determination by public administration bodies, in particular at the local level, of priority directions for attracting charitable funds from entrepreneurs in order to limit the scope of charitable objects, in which an increased amount of tax deduction is granted, for example, restoration of destroyed educational institutions, etc.; thirdly, increasing the participation of local public administration bodies (primarily local self-government bodies and local state administrations) in information support of business entities by promoting in social networks and other information platforms up-todate information about the socio-economic state of regions, individual administrative territorial units, indicating the needs for a certain type of business activity in this area, the advantages of working in a certain area, etc.; fourth, reducing the licensing burden on business entities, as well as transferring licensing powers for certain types of business (for example, the sale of alcoholic beverages) to local public administration bodies; etc.
Keywords: зарубіжний досвід; взаємодія; органи публічного адміністрування; суб’єкти підприємницької діяльності; foreign experience; interaction; public administration bodies; subjects of entrepreneurial activity; зарубежный опыт; взаимодействие; органы публичного администрирования; субъекты предпринимательской деятельности